(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This paper presents a high-gain dual-band microstrip patch antenna array design and simulation for 26/28 GHz 5G applications. The 26 and 28 GHz bands are particularly notable among the existing bands for millimeter-wave applications due to their wide bandwidth and lower absorption rates. The antenna is developed in the CST simulation environment on a Rogers RT5880 substrate with a thickness of 0.508 mm, a relative dielectric permittivity of 2.2, and a loss tangent of 0.0009. The Rogers RT substrate is chosen for its low dielectric loss, controlled dielectric constant, environmental stability, ease of fabrication, and high reliability, making it ideal for high-frequency and high-performance applications. The transmission line model method is used to calculate the antenna dimensions designed to resonate at 26/28 GHz. To achieve high gain and wide bandwidth, arraying and slotting techniques are applied to rectangular patch antennas, as these methods significantly enhance gain, bandwidth, directivity, and radiation pattern control, making them suitable for advanced communication applications. The proposed 1×2 patch antenna array, with dimensions of 33.4 × 21.6 × 0.508 mm³, is designed using a tapered feedline. The antenna array resonates at 26.27 GHz and 28.0 GHz, achieving return losses of -16.55 dB and -31.78 dB, bandwidths of 0.58 GHz and 1.54 GHz, VSWR values of 1.35 and 1.05, gains of 9.12 dB and 12.43 dB, and directivities of 9.77 dBi and 13.05 dBi, respectively. The antenna exhibits higher gain and directivity compared to existing array designs in the literature. This cost-effective and compact antenna array is...